2018
DOI: 10.1007/s12029-018-0128-x
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Sedentary Behavior in Older Gastrointestinal Cancer Survivors: Need and Acceptability of Digital Health Interventions

Abstract: Older GI cancer survivors can benefit from interventions to increase PA and decrease SB. Interest in such interventions was moderate and the acceptability of digital health tools for these interventions was limited. At the present time, behavioral interventions for older GI cancer survivors should not be delivered exclusively through digital tools and strategies to improve adoption of various technologies should be implemented when using these tools to modify PA and SB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
2
2
0
Order By: Relevance
“…This finding has to be taken into consideration when designing digital interventions. Similar results regarding the use of digital interventions in older patients were previously observed [ 38 ]. Nevertheless, older patients are not to be neglected in terms of the development of digital interventions as the aging population is expected to become increasingly accustomed to the use of smart technologies [ 39 ].…”
Section: Discussionsupporting
confidence: 88%
“…This finding has to be taken into consideration when designing digital interventions. Similar results regarding the use of digital interventions in older patients were previously observed [ 38 ]. Nevertheless, older patients are not to be neglected in terms of the development of digital interventions as the aging population is expected to become increasingly accustomed to the use of smart technologies [ 39 ].…”
Section: Discussionsupporting
confidence: 88%
“…The range of attitudes, and the belief that DI should supplement traditional healthcare, are consistent with previous literature ( 40 , 49 , 50 , 54 ). Similarly, participants believed that DI is likely to benefit people with mild conditions ( 40 , 55 , 56 ), further suggesting that healthcare consumers want DI to complement the existing healthcare system rather than replace it.…”
Section: Discussionsupporting
confidence: 87%
“…Despite attitudes influencing the likelihood of using DI, surprisingly, little is known about the attitudes people hold. Attitudes about DI for physical health have rarely been studied, with few existing studies suggesting somewhat positive attitudes ( 49 , 50 ). Attitudes about DI for mental health have been more widely studied, perhaps as DI are more commonly used to support mental health.…”
Section: Introductionmentioning
confidence: 99%
“…Despite beneficial effects of exercise, adherence to physical exercise guidelines in people living with cancer remains low. It is reported that 12.4%–22% of cancer survivors meet the recommended level of physical activity (Hawkes et al., 2013; Sanders et al., 2018). Altogether, people living with cancer face challenges in maintaining optimal physical and psychological functioning and are at greater risk for reduced health‐related quality of life.…”
Section: Introductionmentioning
confidence: 99%